Climate change, gender, and nutrition: Support to USAID programs in Nigeria - Thomas, Timothy S.; Bryan, Elizabeth; Choufani, Jowel; Azzarri, Carlo; Bhandary, Prapti; Ngugi, Moffatt; Buzzard, Robert (International Food Policy Research Institute, 2017)
Increasing temperature, erratic rainfall, and other extreme events, such as floods and droughts, pose severe threats to development in Nigeria. Climate change will have significant adverse impacts on crop production and livelihoods, making the country’s poor and disadvantaged people even more vulnerable. It is imperative that the impact of relevant climate science on agricultural production be considered, together with important cross-cutting issues that influence agricultural growth, poverty alleviation, and climate resilience—especially gender and nutrition—if the goals of Feed the Future and the Global Food Security Strategy are to be achieved. This policy note summarizes assessments of these interlinkages in the Nigerian context under the Gender, Climate Change, and Nutrition Integration Initiative (GCAN).